PENGARUH BUDAYA ORGANISASI DAN MOTIVASI BERPRESTASI TERHADAP KINERJA KEPALA SEKOLAH - Darusman Taufik (Universitas Negeri Jakarta, 2010)
The objective of the research is to obtain the direct effect of organizational culture and achievement motivation on the headmasters’ performance. The study was conducted at Bangka Regency and Pangkalpinang town in Bangka Belitung Province in 2010 by using a survey method with path analysis applied in testing hypothesis and 36 samples selected by simple random sampling.The finding of the research are: (1) there is a positive direct effect of organizational culture on headmasters’ performance; (2) there is a positive direct effect of achievement motivation on headmasters’ performance; and (3) there is a positive direct effect of organizational culture on achievement motivation.Based on these findings, it could be concluded that any changing or variation occured at headmasters’ performance might have been directly significant effected by achievement motivation and organizational culture.Therefore, when we want to minimaze the variation which occurred in headmasters’ performance, these factors such as achievement motivation and organizational culture are necessary to be taken into account.